Multivisceral resection of nonfunctional pancreatic neuroendocrine neoplasm with nearby organ invasion: a case report - Zhang, Cong; Niu, Weiqiao; Xu, Yaopeng; Lu, Yijie; Huang, Lining; Li, Song; Jiang, Xinwei; Wu, Jianwu (Frontiers in Endocrinology, 2023)
Pancreatic neuroendocrine neoplasms (pNENs) are relatively rare epithelial malignancies originating from pancreatic neuroendocrine cells, pathologically classified into well-differentiated pancreatic neuroendocrine tumors (pNETs) and poorly-differentiated pancreatic neuroendocrine carcinoma (pNECs). Although they also fall under the category of pNENs, the almost entirely distinct biological characteristics and survival prognosis have caused debate among surgeons when it comes to the development of surgical intervention options, particularly for locally advanced G3 pNETs and pNECs. We present a case of 66-year-old male with nonfunctional G3 pNET, invasion of five nearby pancreatic organs and type II liver metastases. The patient achieved good outcomes after undergoing multivisceral resection and postoperative adjuvant chemotherapy. This finding helps surgeons better understand locally advanced pNENs, formulate treatment decisions systematically and confidently, and balance patient benefits and risks of surgery.